Model Asesmen Praktikum Kimia untuk Siswa SMA pada Kurikulum Merdeka Belajar - siswaningsih, wiwi; Nahadi; Dewi, Syifa Aulia; Lutvia, Dhea (LPPM Universitas Negeri Jakarta, 2024)
The independent learning curriculum that is currently implemented requires adjustments in the learning process, one part of which is assessment. This study aims to create an assessment model in the independent learning curriculum in the Mass Conservation of Law practicum using Moodle. The assessment model created is in the form of a performance assessment that uses Moodle media as a platform. The method used is descriptive statistical method. The sample used was 14 students of class X IPA one off SMAN Kota Bandung. The instrument used is an observation sheet rubric and task containing aspects of performance skills in the Law of Conservation of Mass practicum. The results obtained are the chemistry practicum assessment model using Moodle LMS, which can describe students' performance abilities in real practicum. Thus the assessment model using the Moodle LMS can be used as an alternative in assessing the performance student of the mass conservation law practicum in the independent learning curriculum in high school.